The Effectiveness of Article 127b of Permen ATR/KPBN No. 16 of 2021 On The Implementation of The Registration of PPJB Deeds and Lease Agreements For Registered Land At The Land Office (A Study In Malang Raya) - Sayoko, Wahyu Rekso; Negara, Tunggul Anshari Setia; Susilo, Hariyanto (IJBLE Scientific Publications Community Inc., 2025)
This study examines the effectiveness of Article 127b of Permen ATR/BPN Number 16 of 2021, which pertains to the registration of Deeds of Sale and Purchase Agreements (PPJB) and Deeds of Lease on registered land at the Land Office. The legal issue raised is the discrepancy between das sein (the reality on the ground) and das sollen (the legal provisions that should apply). In the Malang Raya region, these provisions are often overlooked or not implemented as they should be, resulting in numerous disputes over land and buildings based on PPJB and lease agreements. This study employs an empirical method grounded in theories of legal effectiveness, legal certainty, and legal utility. The results of the study indicate that the implementation of Article 127B has been ineffective because the three indicators of legal effectiveness—legal Substance, legal Structure, and legal culture—have not been met. The primary causes are the inadequate enforcement of regulations and a lack of understanding among relevant parties regarding the registration mechanism. Therefore, technical guidelines, as well as socialization and training, are necessary to enhance the effectiveness of implementing this article and prevent disputes in the future.